Arthroscopically Assisted Reduction and Internal Fixation for Tibial Plateau Fractures - Mainak Roy; Madhan Jeyaraman; Naveen Jeyaraman; Ashok Shyam (Journal of Orthopaedic Case Reports)
Tibial plateau fractures are complex intra-articular injuries resulting from high-energy trauma in young patients or low-energy mechanisms in osteoporotic individuals. Proper management is crucial to restore joint congruity, stability, and function, ultimately preventing long-term complications such as post-traumatic osteoarthritis. Open reduction and internal fixation have been the traditional approach but are associated with significant morbidity, including extensive soft-tissue damage and infection risk. Arthroscopically assisted reduction and internal fixation have emerged as a minimally invasive alternative that allows for precise fracture reduction, direct assessment of intra-articular soft-tissue injuries, and lower complication rates. This review discusses the indications, surgical technique, advantages, limitations, outcomes, and future perspectives of ARIF in the management of tibial plateau fractures.